Case Report: Hypercholesterolemia “Lean Mass Hyper-Responder” Phenotype Presents in the Context of a Low Saturated Fat Carbohydrate-Restricted Diet - Norwitz, Nicholas G.; Soto-Mota, Adrian; Feldman, David; Parpos, Stefanos; Budoff, Matthew (Frontiers in Endocrinology, 2022)
Emerging evidence suggests that “leanness” and good metabolic health markers may predict larger increases in LDL cholesterol (LDL-C) in response to carbohydrate restriction. Specifically, a recent cohort study demonstrated an inverse association between BMI and LDL-C change among individuals on carbohydrate-restricted diets and identified a subgroup of “Lean Mass Hyper-Responders” (LMHR) who exhibit exceptional increases in LDL-C, in the context of low triglycerides and high HDL-C. We present the case of one subject, LM, who adopted a ketogenic diet for management of ulcerative colitis. He subsequently experienced an increase in LDL-C from 95 to 545 mg/dL, at peak, in association with HDL-C >100 mg/dL and triglycerides ~40 mg/dL, typical of the emergent LMHR phenotype. Assessments of LM’s dietary intake, lipid panels, and BMI are consistent with prior data and suggest that the LMHR phenomena is not dependent on saturated fat intake but inversely associates with BMI changes. Finally, computed tomography angiography conducted on LM after over 2-years of hypercholesterolemia revealed no evidence of calcified or non-calcified plaque.